Komunikasi Dakwah Ustadz Syaiful Anwar di Desa Semayap, Kecamatan Pulau Laut Utara, Kabupaten Kotabaru, Provinsi Kalimantan Selatan - Surya, Muhammad Naufal; Pardianto, Pardianto (Journal of Management, Education and Communication, 2024)
The aim of this research is to describe the communication methods of Ustadz Syaiful Anwar's preaching in Semayap Village, Pulau Laut Utara District, Kotabaru Regency, South Kalimantan Province. This research method uses a qualitative descriptive research type. The theory used to analyze the research results is Aristotle's rhetorical theory. The results of this research show that Ustadz Syaiful Anwar's da'wah communication method in preaching uses 3 (three) ways; First, Ustadz Syaiful Anwar uses intonation in his preaching. Intonation and tempo are used so that the audience is interested and continues to follow the lecture. Second, Ustadz Syaiful Anwar uses popular language styles based on word choice, namely conversational language style, language style based on tone, language style based on sentence structure, and direct language style. Third, Ustadz Syaiful Anwar uses an elegant style and gesture, namely; In preaching communication, he stands calmly, straight and firm, his facial expressions and hand movements when he smiles, laughs, and his eyes are always directed towards the audience